Media consumption in Malaysia a hermeneutics of human behaviour - Wilson, Tony 1947- (Routledge contemporary Southeast Asia series, 2015)
The volume provides an account of practices theory from its origins in critical hermeneutics (such as Heidegger, Gadamer and Ricoeur), as reflecting on the processes of embodied understanding, developing alongside interpretive and reception theory. Part I draws upon authors as diverse as Heidegger and Henry Jenkins, with a practices perspective on media and mall consuming shown as developing from forty years of theorizing about audience activity. An empirical study of Malaysian blogging and branding on YouTube exemplifies this approach. Part II considers Malaysians absorbed in social media sites, as everyday visitors and the subjects of consumer research. The book then returns to the material world, exploring the horizons of understanding from which Malaysians enter their mediated malls, and concludes by positioning media practices theory within a spectrum of philosophical ideas.